Diseño de un manual pedagógico para aplicar la dramatización como estrategia metodológica para los octavos años de educación básica en el Colegio “Nacional Mulaló” en la parroquia Mulaló, cantón Latacunga durante el año lectivo 2012-2013 - Maigua Muela, Marco Paúl (2015)
The ain of the investigation is to shaw what the students obtain from academic activities with their social studies showing the process and dramatization, were we will see in a positive from the learning way of positive from the learning way of the students the eight grade in the “National Mulaló” college in Latacunga town. Whithin the investigation we took account the use of a pedagogical hand book as a dependent variable and the learning as the dependent variable, we were able to curry out this whith our bibliography research trough the information provided by the internet, books and texts. The research field was carried out by asking and family members to were we observed the differents problems of the learning information obtained by the students within our table graphs and analysis, we translated the information, saw the problem and faind the sanction with recommendation that we applied in the final dramatization were our goal was to improve the academic development for the students.